Pengaruh Gadget Addiction terhadap Kecemasan Akademik Siswa TJKT SMK Negeri 2 Banjarmasin: The Influence of Gadget Addiction on Academic Anxiety of TJKT Students at SMK Negeri 2 Banjarmasin - Anisyah Puan Maharani; Nina Permata Sari; Muhammad Arsyad (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Students at the secondary education level, especially in vocational high schools, face various academic demands that require cognitive and emotional readiness. The development of digital technology has made gadgets an inseparable part of students' lives, both for academic and non-academic purposes. However, uncontrolled gadget use has the potential to lead to gadget addiction, which can disrupt learning concentration, reduce effective learning time, and increase academic stress. This condition can trigger academic anxiety in students. Therefore, it is important to examine the effect of gadget addiction on students' academic anxiety. This study aims to analyze the effect of gadget addiction on the academic anxiety of students majoring in Computer Network and Telecommunication Engineering (TJKT) at SMK Negeri 2 Banjarmasin. This study uses a quantitative approach with an influence research type. The research sample consisted of 89 students, selected through a cluster sampling technique. Data were collected using a gadget addiction scale and an academic anxiety scale, and analyzed using simple linear regression. The results of the analysis show that gadget addiction has a positive and significant effect on students' academic anxiety, as evidenced by a regression significance value of <0.05 and a coefficient of determination of 0.244. Thus, it can be concluded that gadget addiction is one of the factors contributing to increased academic anxiety in students.